A method for analyzing stability of tower-line system under strong winds. (January 2019) - He, Bo; Zhao, Mingxi; Feng, Wentao; Xiu, Yaping; Wang, Yu; Feng, Lijun; Qin, Yongjian; Wang, Chukun
Highlights: This study proposed an effective method for analyzing the stability of tower-line system under strong wind. The comparison between static and dynamic loads was conducted which has a good guiding effect on the wind resistance level design of transmission lines and the explanation of the accident records. The relationship among the largest stress value, wind speed and wind direction was established, and the stability limit of the transmission line was evaluated in this paper. Abstract: Typhoon is a kind of bad weather affecting the safety of overhead transmission lines seriously. In recent years, mechanical failures, such as tower collapse and strand breakage from strong winds, have frequently occurred in coastal typhoon-prone areas in China. From the view of mechanics, the transmission lines should be considered as a tower-line coupling system entirety and dynamic loads should be taken into account. However, existing design specifications are insufficient for the consideration of dynamic loads. To analyze the stability of the tower-line system, the wind-induced response of the system was evaluated-with the tower-line coupling considered-by finite element modeling, and an effective method was introduced. Firstly, a finite element model containing three towers and two line segments was set up in accordance with actual transmission lines having a disaster history of strong wind. Secondly, static and dynamic wind loads were applied to the model, and the stress distribution was simulated. Thirdly, the relationship among the largest stress value, wind speed and wind direction was established, and the stability limit of the transmission line was evaluated. The method showed good efficiency in evaluating the mechanical properties of the tower-line coupling system under strong wind conditions, and the results are consistent with accident records.